Neural practice effect during cross-modal selective attention: Supra-modal and modality-specific effects. (September 2018) - Xia, Jing; Zhang, Wei; Jiang, Yizhou; Li, You; Chen, Qi
Abstract: Practice and experiences gradually shape the central nervous system, from the synaptic level to large-scale neural networks. In natural multisensory environment, even when inundated by streams of information from multiple sensory modalities, our brain does not give equal weight to different modalities. Rather, visual information more frequently receives preferential processing and eventually dominates consciousness and behavior, i.e., visual dominance. It remains unknown, however, the supra-modal and modality-specific practice effect during cross-modal selective attention, and moreover whether the practice effect shows similar modality preferences as the visual dominance effect in the multisensory environment. To answer the above two questions, we adopted a cross-modal selective attention paradigm in conjunction with the hybrid fMRI design. Behaviorally, visual performance significantly improved while auditory performance remained constant with practice, indicating that visual attention more flexibly adapted behavior with practice than auditory attention. At the neural level, the practice effect was associated with decreasing neural activity in the frontoparietal executive network and increasing activity in the default mode network, which occurred independently of the modality attended, i.e., the supra-modal mechanisms. On the other hand, functional decoupling between the auditory and the visual system was observed with the progress of practice, which varied as a function of the modality attended. The auditory system was functionally decoupled with both the dorsal and ventral visual stream during auditory attention while was decoupled only with the ventral visual stream during visual attention. To efficiently suppress the irrelevant visual information with practice, auditory attention needs to additionally decouple the auditory system from the dorsal visual stream. The modality-specific mechanisms, together with the behavioral effect, thus support the visual dominance model in terms of the practice effect during cross-modal selective attention.